2020
DOI: 10.3390/medicina56070358
|View full text |Cite
|
Sign up to set email alerts
|

Progression to Severe Hypernatremia in Hospitalized General Medicine Inpatients: An Observational Study of Hospital-Acquired Hypernatremia

Abstract: Background and objectives: Hypernatremia can be community or hospital-acquired, and there may be specific factors unique to the hospital environment, such as intravenous fluid treatment, which contribute to hypernatremia. The aim of this study was to determine the factors associated with the progression from moderate to severe hospital-acquired hypernatremia among patients admitted under general medicine. Materials and Methods: In this retrospective, single-center cohort study (2012 to 2017), we used ICD-10 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
2
8
0
1
Order By: Relevance
“…This report confirms previous observations relating hospital-acquired hypernatremia and its severity to mortality in hospitalized patients 1,4,7,10,11 and extends previous research by examining discharge dispositions. Our findings for increment of in-hospital mortality along with the increase in the severity of hypernatremia are similar to other studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This report confirms previous observations relating hospital-acquired hypernatremia and its severity to mortality in hospitalized patients 1,4,7,10,11 and extends previous research by examining discharge dispositions. Our findings for increment of in-hospital mortality along with the increase in the severity of hypernatremia are similar to other studies.…”
Section: Discussionsupporting
confidence: 90%
“…47 Outcomes of hypernatremia have also been less studied, and most studies examined selected patient populations. 1,4,810 In addition, there are limited studies regarding hospital-acquired hypernatremia 11 and patients' kidney function at admission.…”
Section: Introductionmentioning
confidence: 99%
“… 47 Studies have found that the increase of serum creatinine was closely related to the progression of severe hypernatremia. 35 At the time of hypernatremia, patients are usually still being treated with normal saline, which may worsen the hypernatremia. 12 However, we also recognized that there were many reasons for elevated serum creatinine that might not be explained.…”
Section: Discussionmentioning
confidence: 99%
“…10,[30][31][32][33][34] A study found that the hospital mortality rate of patients with hospital-acquired hypernatremia was 29%. 35 However, it is unclear whether hypernatremia directly reduces survival or whether it is a surrogate marker for more severe disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Padidėjęs laisvo vandens netekimas sukelia hipernatremiją. Karščiavimas yra dažnas veiksnys, kuris paskatina hipovoleminės hipernatremijos atsiradimą [2,3,6]. Viduriavimas -kita priežastis, dėl kurios prarandamas hipotoninis vanduo.…”
Section: Hipernatremija Intensyviojoje Terapijojeunclassified